Comparative anatomy of the vertebrates - Kent, George C.; Carr, Robert K (Biological Science Series, 2001)
Deemed a classic for its reading level and high-quality illustrations, this respected text is ideal for your one-semester Comparative Anatomy course. For the ninth edition, George Kent is joined by new co-author Bob Carr.